Suitable harvesting stage and effect of 1-methycyclopropene on postharvest quality of soursop (Annona muricata L.) - Lem, Ming Siang (2018)
Soursop (Annona muricata L.) known to be climateric fruit, rich in bioactive compounds for use in medicine, produce aromatic, sweet-sour and pleasantly tasting. There is, however, a limitation in reaching distant markets stems from quick ripening and accentuated softening that make fruits difficult to handle without damage and shortens postharvest life. In order to reduce lost in profits during storage life, this study aims to determine the optimum harvest stage and the effect of 1- Methylcyclopropene (1-MCP) treatment on postharvest life, physiological and physiochemical characterization of soursop. In the first experiment, soursop flowers were hand pollinated and tagged. Successful pollinated fruits were harvested from 12th weeks after pollination. Results showed that harvesting period from weeks 16 to 20 after pollination did not affect physicochemical quality such as respiration rate, ethylene production, soluble solids concentration, titratable acidity, ascorbic acid and pH for these fruits. Optimum harvest for soursop was indicated by peel colour change and decrease firmness which proximity with the physiological maturity along with maturity of seeds. Also, results indicated that soursop fruit start maturation and ripening from the distal part of fruit. In second experiment, fruits were harvested at 16th weeks after pollination selected for treated with various concentration of 1-MCP (0, 400, 800 and 1200 nL/L) at 15°C + 3°C for 24 hours and then stored at ambient temperature (25°C + 3°C). Observations on various physical, physiological, biochemical and antioxidants parameters were recorded at two days intervals during 6 days of storage. Result showed soursop treated at different 1-MCP concentration (0, 400, 800 and1200 nL/L) showed that fruit treated with 400 nL/L had better ripe fruit quality. In additional, 1-MCP treated fruits were able to normally soften at later ripening stage. However, antioxidant capacity, total phenolic content, and total flavonoid content of fruits from all treatments were found to be inconsistent during storage.